RARE EARTH ELEMENTS IN ROCKS AND MINERALS FROM ALKALINE PLUTONS OF THE KOLA PENINSULA, NW RUSSIA, AS INDICATORS OF ALKALINE MAGMA EVOLUTION - Arzamastsev A.A.; Arzamastseva L.V.; Bea F.; Montero P. (My University, 2002)
In order to elucidate evolutionary paths for the alkaline ultramafic series of the Kola province, we studied distribution of rare earth elements (REE) in rocks and constituent minerals of the rock sequence dunite, clinopyroxenite, melilitolite, meltejgite, ijolite, nepheline syenite. Abundances of REE and other trace elements were measured in olivine, melilite, clinopyroxene, nepheline, apatite, perovskite, titanite, and magnetite. Distribution of most trace elements in Kovdor-type rocks is shown to differ fundamentally from that in the Khibiny alkaline ultramafic suite and to have been controlled by perovskite crystallization. Primary olivine melanephelinitic melts of the Kovdor series are demonstrated to be characterized by early crystallization of perovskite, the most important REE mineral. Perovskite co-precipitating with olivine and clinopyroxene leads to a sharp REE depletion of the residual melt, to produce REE-depleted derivatives, ijolites and nepheline syenites. By contrast, the genesis of the Khibiny alkaline ultramafic series was complicated by mixing of minor batches of phonolitic melt with the primary olivine melanephelinitic magma, which led to changes in the crystallization order of REE-bearing titanates and Ti-silicates and to enrichment of late melt batches in the most incompatible elements. As a result, Khibiny ijolites have the highest REE abundances, which are accommodated by high-REE apatite and titanite.
Keywords: RARE-EARTH ELEMENTS; ALKALINE PLUTONS; ALKALINE MAGMA EVOLUTION; KOLA PENINSULA